Comparison of the Performance of Lateral and Vertical InGaN/GaN-Based Light-Emitting Diodes with GaN and AlN Nucleation Layers. (1st January 2016) - Kang, Daesung; Jung, Myunghoon; Choi, Eunsil; Song, Kiyoung; Jeong, Hwanhee; Song, June-O; Kim, Da-Som; Kim, Sun-Kyung; Seong, Tae-Yeon
Abstract : We investigated the effects of in situ GaN and sputtered AlN nucleation layers on the output power of GaN-based blue (445 nm) LEDs on patterned sapphire substrate (PSS) and planar sapphire substrates. Both the PSS LEDs and planar LEDs showed the same operation voltages, but the LEDs with the AlN layer had much lower reverse leakage current at −15 V. The LEDs with the AlN layer showed higher external quantum efficiency (EQE) at low current regions than those with the GaN nucleation layer. However, the AlN nucleation layer LEDs experienced a little more severe efficiency droop than did the GaN layer LEDs. It was shown that the AlN nucleation layer samples contained fewer defects than the GaN nucleation layer samples. The Raman spectral results showed that the AlN nucleation layer samples experienced higher compressive stress than the GaN nucleation layer samples. Simulation results also showed that both the AlN nucleation layer and air voids in the GaN nucleation layer samples hardly affected the light extraction efficiency. Based on the electrical, X-ray diffraction (XRD), cathodoluminescence (CL), and Raman results, the electrical behavior of the PSS and planar LEDs are described and discussed.